Thiazolidinedione use is associated with reduced risk of Parkinson’s disease in patients with diabetes: a meta-analysis of real-world evidence - Hussain, Salman; Singh, Ambrish; Baxi, Harveen; Taylor, Bruce; Burgess, John; Antony, Benny (Neurological sciences, 2020)
Background The thiazolidinedione (TZD) class of oral antidiabetic agents are used to treat type 2 diabetes mellitus (DM). This meta-analysis aimed to understand the protective effect of TZD on Parkinson’s disease (PD) in people with diabetes. Method A literature search was performed in PubMed, Embase, and Cochrane central from inception to until 30 September 2019. We included all real-world evidence studies assessing the use of TZD class of drugs and the risk of PD in people with diabetes. Quality of the studies was evaluated using the Newcastle-Ottawa scale. The primary outcome was the pooled hazard ratio (HR) of PD among type 2 DM TZD users as compared with TZD non-users in people with diabetes. The secondary outcome was the HR of PD among type 2 DM TZD users as compared with non-users (include both diabetic and nondiabetic population). Meta-analysis was performed using RevMan software. Results Out of five studies selected for inclusion, four studies fulfilled the criteria for primary outcomes. The participants’ mean age and follow-up duration were 66.23 ± 9.59 years and 5.25 years (2.97–7.9 years), respectively. There was a significant reduction in the risk of PD (pooled adjusted HR of 0.81 [95% CI 0.70–0.93, p = 0.004]) in TZD users compared with non-TZD users in people with diabetes. A significant protective effect of TZD was observed in Caucasian population (3 studies) (HR 0.78 (95% CI 0.66–0.92), p = 0.003). Conclusion This meta-analysis demonstrates a potential neuroprotective effect of TZD for PD risk in the population with DM.